MORAL DECADENCE OF URBAN MUSLIMS: A CONTEXTUAL ANALYSIS THE VERSES OF AL-AMR BI AL-MA'R?F WA AL-NAHY 'AN AL-MUNKAR IN ANSWERING THE ETHICAL CRISIS IN PADANG CITY - Zulfi Akmal; Muhammad Bin Suhaimi (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2025)
Padang City represents a prominent model of Islamic and customary value integration through the local philosophical construct “Adat Basandi Syarak, Syarak Basandi Kitabullah”(ABS-SBK). However, contemporary social dynamics have revealed a significant moral decline, as evidenced by the increasing prevalence of LGBT phenomena, promiscuity, drug abuse, youth violence, and the erosion of ethical awareness and modesty. This study aims to analyze the ethical crisis among urban Muslims in Padang using a thematic tafsir (tafsir mawdu’i) approach to the Qur’anic concept of al-Amr bi al-Ma‘r?f wa al-Nahy ‘an al-Munkar. Employing qualitative field research with Miles and Huberman’s triangulation model, the study integrates perspectives from ‘ul?m al-Qur’an, hadith, and the phenomenology of religion. The findings reveal three key insights: First, the primary cause of moral decay lies not in modernity itself but in the lack of ethical consciousness to critically engage with it; Second, the proliferation of religious symbols in public spaces does not correlate with genuine spiritual depth, leading to artificial religiosity; and Three, formal regulations, including Islamic Regional Bylaws and local policies, remain ineffective due to weak transformative approaches and the emergence of social mechanisms that justify deviant behaviors. The study concludes that it is imperative to reconstruct the value of al-Amr bi al-Ma‘r?f wa al-Nahy ‘an al-Munkar in urban contexts by grounding it in Qur’anic ethics and Minangkabau local wisdom. This research contributes to the development of a relevant and applicable model of Islamic social ethics in contemporary urban settings. It recommends public policy reforms to foster a deeper and more practical understanding of Islam. Without such systemic reform, ABS-SBK risks becoming a hollow cultural slogan preserved in name but devoid of transformative meaning.